Synthesis, thermal behavior and spectroscopic study of trivalentlanthanide and yttrium(III) α-hydroxyisobutyrates, in solid state - Caires, F. J. [UNESP]; Gigante, A. C. [UNESP]; Gomes, D. J C [UNESP]; Treu-Filho, O. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier, 2013)
Thermal and spectroscopic studies on solid trivalent lanthanides and yttrium(III) α-hydroxyisobutyrates, Ln(C4H7O 3)3·nH2O were investigated employing simultaneous thermogravimetry and differential thermal analysis (TG-DTA), elemental analysis, X-ray diffractometry, complexometry, experimental and theoretical infrared spectroscopy and TG-DSC coupled to FTIR. The dehydration of lanthanum to neodymium and terbium to thulium and yttrium compounds occurs in a single step while for samarium, europium and gadolinium ones it occurs in three consecutives steps. Ytterbium and lutetium compounds were obtained in the anhydrous state. The thermal decomposition of the anhydrous compounds occursin two consecutives steps, except lanthanum (five steps) and cerium (single step), with formation of the respective oxides CeO2, Pr6O 11, Tb4O7 and Ln2O3 (Ln = La, Nd to Lu and Y), as final residue. The resultsalso provided information concerning the composition, thermal behavior, crystallinity and gaseous products evolved during the thermal decomposition. The theoretical and experimental spectroscopic data suggested the possible modes of coordination of the ligand with the lanthanides.© 2013 Elsevier B.V.
Keywords: α-Hydroxyisobutyrate; Lanthanides and yttrium; Theoretical infrared spectroscopy; Thermal behavior; Anhydrous compounds; Crystallinities; Gaseous products; Information concerning; Spectroscopic data; Spectroscopic studies; Thermal behaviors; Trivalent lanthanides; Cerium compounds; Decomposition; Differential thermal analysis; Europium compounds; Gadolinium compounds; Infrared spectroscopy; Lanthanum; Lanthanum compounds; Lanthanum oxides; Spectroscopic analysis; Thermogravimetric analysis; X ray diffraction analysis; Yttrium; Yttrium alloys